ANALISA SISTEM PENGENDALIAN INTERNAL TERHADAP PROSES KELUAR-MASUK BARANG PADA PERUSAHAAN LOGISTIK DEPARTEMEN GUDANG STUDI PADA PT CIPTA KRIDA BAHARI - Aisyah, Aulia Khusnul (Jurnal Ilmiah Mahasiswa FEB, 2013)
The purpose of this study was to determine whether the practice of information systems that run was in accordance with the procedures set by the company, and to determine the factors that may affect the lead time of the process out of the goods. The research method used is descriptive method of analysis, a method that aims to describe the company based on the fact that actually occur in the company. The data needed in this study include standard operating procedures (SOP), flow charts, applications related to accounting information systems especially in the process of handing over the goods at PT Cipta Krida Bahari Warehouse Department Surabaya branch. Based on the results of research and discussion, it can be concluded that the entry and exit of goods at CKB PT Surabaya branch already meet the standards set by the company. Internal factors which influence the process out of the lead time items such as a lack of communication between the warehouseman, demand for goods that do not fit through the admin barn, and an error in the data updates outstanding. While external factors affecting the length of time the process of getting tungya tally sheet, checker and a forklift operator voters. Keywords: Internal Control